The role of information technology in enhancing the banking sector - Edan, Fryal Mushraf (International journal of economic perspectives, 2024)
The topic of information technology is one of the important topics affecting the banking sector in general, in today’s world, in light of the trend towards spreading the presence of the information and technology sector in general in all aspects of the banking sector. The problem that the research deals with is related to the role that information technologies can play in improving the performance of the banking sector, including the quality of that sector. The research reached a number of conclusions, related to the fact that information technologies (human resources skills, databases, communication networks and software) affect enhancing the quality of banking service. The research leads to a general recommendation, which is: the necessity of paying attention to information technologies, and working to develop them continuously due to their effective contribution to the success of the services provided by the banking sector.